2022
DOI: 10.3389/fmolb.2021.785767
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1/lncRNA TYMSOS/miR-214-3p–Mediated High Expression of NCAPG Correlates With Poor Prognosis and Cell Proliferation in Non–Small Cell Lung Carcinoma

Abstract: Lung cancer is the most common cancer with high mortality. Increasing evidence has demonstrated that nonstructural maintenance of chromosomes condensin I complex subunit G (NCAPG) plays a crucial role in the progression of human cancers. However, the biological function and underlying mechanism of NCAPG in non–small cell lung cancer (NSCLC) are still unclear. Here, we utilized diverse public databases to analyze the expression of NCAPG in pan-cancer. We found that NCAPG was highly expressed in various human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Emerging evidence has demonstrated that tumor mutational burden (TMB) and microsatellite instability (MSI) could be a potential biomarker for predicting the efficacy of immunotherapy for lung cancer ( 29 ). The above findings indicated that the IRRGs were related to tumor immune infiltration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has demonstrated that tumor mutational burden (TMB) and microsatellite instability (MSI) could be a potential biomarker for predicting the efficacy of immunotherapy for lung cancer ( 29 ). The above findings indicated that the IRRGs were related to tumor immune infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative real-time PCR (qRT-PCR) assay was performed as documented ( 29 ). The primer sequences are list follows: SNHG17-F, GATTGTCAGCTGACCTCTGTC; SNHG17-R, GTGGTAGCCTCACTCTCCATTCTCTGCCCCT; β-actin-F, CTTCGCGGGCGACGAT; and β-actin-R, CCATAGGAATCCTTCTGACC.…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration and invasion assay was performed as previously documented ( 20 ). For transwell assay, 2.5×10 4 cells in 100 μl of serum-free medium were plated in a 24-well plate chamber insert, with medium containing 10% FBS at the bottom of the insert.…”
Section: Methodsmentioning
confidence: 99%
“…The qRT-PCR assay was performed as documented ( 29 ). The primer sequences are list follows: miR-195-5p-F: GAATTCGCCTCAAGAGAACAAAGTGGAG, miR-195-5p R: AGATCTCCCATGGGGGCTCAGCCCCT; U6-F: GGTCGGGCAGGAAAGAGGGC, U6-R: GCTAATCTTCTCTGTATCGTTCC, PTBP1-F: AGCGCGTGAAGATCCTGTTC, PTBP1-R: CAGGGGTGAGTTGCCGTAG, β-actin-F: CTTCGCGGGCGACGAT, β-actin-R: CCATAGGAATCCTTCTGACC.…”
Section: Methodsmentioning
confidence: 99%